Bibliometric Analysis of Female Authorship Trends and Collaboration Dynamics Over JBMR's 30‐Year History. (6th September 2017) - Wininger, Austin E; Fischer, James P; Likine, Elive F; Gudeman, Andrew S; Brinker, Alexander R; Ryu, Jonathan; Maupin, Kevin A; Lunsford, Shatoria; Whipple, Elizabeth C; Loder, Randall T; Kacena, Melissa A
ABSTRACT: In academia, authorship is considered a currency and is important for career advancement. As the Journal of Bone and Mineral Research ( JBMR ) is the highest‐ranked journal in the field of bone, muscle, and mineral metabolism and is the official publication of the American Society for Bone and Mineral Research, we sought to examine authorship changes over JBMR 's 30‐year history. Two bibliometric methods were used to collect the data. The "decade method" included all published manuscripts throughout 1 year in each decade over the past 30 years starting with the inaugural year, yielding 746 manuscripts for analysis. The "random method" examined 10% of published manuscripts from each of the 30 years, yielding 652 manuscripts for analysis. Using both methods, the average number of authors per manuscript, numerical location of the corresponding author, number of collaborating institutions, number of collaborating countries, number of printed manuscript pages, and the number of times each manuscript was cited all significantly increased between 1986 and 2015 ( p  < 10 −4 ). Using the decade method, there was a significant increase in the percentage of female first authors over time from 35.8% in 1986 to 47.7% in 2015 ( p  = 0.02), and this trend was confirmed using the random method. The highest percentage of female first authors in 2015 was in Europe (60.0%), and Europe also had the most dramatic increase in female first authors over time (more than double in 2015 compared with 1986). Likewise, the overall number of female corresponding authors significantly increased during the past 30 years. With the increasing demands of publishing in academic medicine, understanding changes in publishing characteristics over time and by geographical region is important. These findings highlight JBMR 's authorship trends over the past 30 years and demonstrate those countries having the most changes and where challenges still exist. © 2017 American Society for Bone and Mineral Research.